Il Piemonte alla prova dell’economia della conoscenza - Carlo Genova (Quaderni di Sociologia, 2015)
At the basis of the five volumes of the project ERICA there is the hypothesis that the development of a knowledge economy and of a knowledge society widely depends on the interaction between the different ways of producing knowledge, on the work of the different institutional spheres, and on the learning and cooperation mechanisms acting in local systems. The research aims to study in detail the institutional interventions able to develop collective processes of learning and to reinforce individual skills which are useful for the development of innovation processes. In this perspective, the territory is intended as an “arena” where political and economic entrepreneurs put together their resources to develop innovation processes. School, university, business and family are the fundamental fields of analysis, focusing on the presence and the representations of the knowledge economy in the Piedmont region, looking for indicators able to describe the present and for assumptions to shape the future.